Pengaruh Efikasi Diri Terhadap Kematangan Karir Remaja Akhir di Jorong Kemajuan Nagari Sinuruik Kecamatan Talamau Kabupaten Pasaman Barat - Azia Bertha; Santosa, Budi (Indonesian Research Journal on Education, 2023)
This research is motivated by the phenomenon that occurs in adolescents who do not yet have confidence and readiness in choosing a career to be pursued and the author finds that some of these adolescents do not have the readiness to face the world of work. The approach used is quantitative regression type. The population in this study were late adolescents in Jorong Kemajuan, Kanagarian Sinuruik, TalamauDistrict, West Pasaman Regency, aged 17-18 years, totaling 31 people. The sample in this study were 31 people. In sampling, the writer uses total sampling technique. The total sampling technique is a sampling technique where the number of samples is the same as the population. Data were collected using a questionnaire instrument with a Likert scale type. The data analysis technique used the normality test, linearity test, and hypothesis testing using determination test, simple linear regression test and F test (simultaneous) with the help of SPSS version 20.‎Based on the table above, it is known that the Fcount value is 29,065 with a sig value of 0.000. This case shows that the value of Fcount is greater than Ftable (29.065>4.18) and the value of sig is smaller than than 0.000. Thus, H_0 is rejected and H_1 is accepted, meaning that self-efficacy on career maturity has a significant effect. From these results, it shows that there is a significant effect of self-efficacy on the career maturity of adolescent adolescents in JorongProgress Kanagarian Sinuruik, Talamau District, West Pasaman Regency. Furthermore, the determination index is 50%, meaning that self-efficacy has an influence on career maturity late teens in Jorong Progress, Kanagarian Sinuruik, Talamau District, Pasaman Barat Regency by 50% and 50% is influenced by other factors such as biological, social factors , and the environment.